Estudo do desempenho do multiplexador/demultiplexador ADD/DROP baseado na configuração do interferômetro de Michelson de fibras ópticas para aplicações em sistemas OTDMA E OCDMA - Furtado Filho, Antônio Francisco Gomes (2012)
This work, in addition the chapters which involves both theory and definitions, was basically divided three studies: First (chapter 4), we present a numerical investigation of the performance of a bandpass filter composed of an all-optical directional coupler, followed by two double bars Bragg recorded symmetrically equal outputs in their arms. This configuration features a Michelson interferometer with characteristics of an add/ drop filter. The transmission characteristics (T), extinction rate (XR) and "crosstalk" (XT) were studied based on the application of a CW signal (continuous wave) into the device. Theory of coupled modes and the Runge Kutta fourth order were applied respectively to solve the coupled differential equations. This is the first study considering the nonlinearity of the coupler and the linearity of Bragg gratings. The device features a highly nonlinear behavior as a function of dephasing between the amplitudes of the reflected beams and depending on the input power. In a second step (section 5), the propagation and switching of ultrashort pulse (~ 2PS) Michelson interferometer using an optical fiber. In this study the performance of the interferometer is studied as a function of the nonlinear characteristics of the coupler and Bragg gratings. The numerical studies were made from the coupled mode equations solved using the Runge-Kutta 4th order. The pulse switching characteristics were analyzed as a function of input power and applied to one dephasing Bragg gratings. The transmission characteristics (T), extinction coefficient (XR), "crosstalk" (XT), the compression factor (CF) and shape of the pulses were analyzed for different values of phase and different input powers. We use three values of input power: below the critical power (1W = P0), equal to the critical power (P0 = 1.73W) and above the critical power (P0 = 1.95W). Through this study, it is found that the transmission rate of extinction, "crosstalk" and compression factor depends on the power of the pump device inserted into the gap and applied The Michelson interferometer fiber implement major component with applications in optical networks, such as demultiplexers add/drop. This device has attracted considerable interest in the field of telecommunications due to its ability of high transmission rates. In the third place was presented a numerical simulation study of the performance of encoding and decoding of short optical pulses (ps) systems OCDMA (Optical Code Division Multiple Access based on X FBG (Fiber Bragg Grating ) where codes are inserted through discrete jumps in the optical phase (± π). For generation of coded pulses were used Gold codes obtained analytically. We look at how the inclusion of additional codes affect the autocorrelation and cross correlation. The Michelson interferometer initially studied Chapters 4 was used for propagation and switching of encrypted signals. Based on the characteristics of transmission (T) and extinction rate (XR) did a study of the device as multiplexer / demultiplexer add / drop in the recovery of coded pulses.